Influence of process variables of ECF Ep bleaching stage - Mendez, Claudia Marcela (2009)
Kraft pulp bleaching is difficult, since residual lignin does not dissolve in a single stage with chlorinated compound application. Multiple stages using a significant amount of reagents are necessary to obtain high levels of brightness. The inclusion of hydrogen peroxide in the last alkaline stage of the ECF (Elemental Chlorine Free) bleaching of kraft pulps is at present common practice, as it increases brightness and its stability, besides preserving pulp viscosity and improving the quality of the effluents. The objective of this work consisted in evaluating the process variables of the Ep stage of a pine kraft pulp bleaching process. A fractionated factorial design was initially applied, using as variables the temperature (72ºC – 90ºC), the initial pH (10.5 and 11.5), the initial concentration of H2O2 (0.2% and 0.4% on o.d. pulp – oven-dry pulp), and two types of chelants (DTPA and DTPMPA) at 0.025% on o.d. pulp. A laboratory bleaching was simulated at 10% consistency and 1h residence time. Temperature, initial concentration of H2O2, and pH were the significant variables for the optical pulp properties. An experimental Central Composite Design (CCD) of two factors at five levels was applied with the first two factors, totalling 11 experiments (8 + 3 central point repetitions for pure error determination), a fixed NaOH (% on o.d. pulp) / H2O2 (% on o.d. pulp) ratio equal to 3 having been establishing to maintain the alkalinity. Bleaching processes at different times (5, 10, 20, 45, 90, 180, and 240 minutes) were carried out for each of these experiments, and brightness values higher than 89% ISO were obtained at initial concentrations of 0.25% on o.d. pulp and 0.39% on o.d. pulp of H2O2 at 81ºC, and with 0.35% on o.d. pulp of initial H2O2 at 90ºC and 72ºC, at 180 minutes’ bleaching. The initial concentration of hydrogen peroxide was significant at the different reaction times. At 45 minutes’ reaction (as usually put into practice by the industry for this stage), the maximum brightness values were obtained under the following conditions: T = 81ºC at 0.39% on o.d. pulp of initial H2O2, and T = 90ºC at 0.35% o.d. pulp of initial H2O2. However, it should be observed that the pulp submitted to these last conditions presented higher brightness reversion.